Fabrication of the locally reinforced open-cell nitinol stents for intracranial vascular aneurysm. (31st December 2023) - Han, Rizheng; Yan, Yangyang; Yu, Qiang; Zhang, Zeping; Wang, Qiang; Yang, Rui; Bai, Yun; Zhang, Xing
ABSTRACT: Intracranial vascular stent-assisted coil embolization has been widely used for intracranial vascular aneurysm. However, there are serious complication risks, such as thromboembolism, stent migration and spring coil prolapse, due to the inappropriate radial force, poor wall apposition and oversized mesh. Therefore, a l ocally-reinforced intracranial vascular stent was designed to improve the radial force and wall apposition performance. Based on finite element analysis and substantial measurements, the local radial force has improved 38.9% and thestability of the coil embolism has been enhanced as well. The releasing test in vitro suggests the stent can adhere to the vascular wall very well without the 'Gator backing' phenomenon. Furthermore, the implanting test in vivo shows complete endothelialization without restenosis and hyperplasia in 4 weeks. The outcomes of this study provide optimal design of the locally reinforced nitinol stent used for intracranial aneurysm therapy with reduced risks of vascular embolism and haemorrhagic apoplexy after implantation.